“Trabalhar abelha miúda, ciência da abelha mestre’’: as relações intergeracionais do povo indígena Atikum-umã no sertão de Pernambuco, Brasil (1993-2005) - Silva, Maria das Graças da (2024)
The aim of this paper is to understand the construction of Atikum-Umã intergenerational relations in Pernambuco, experienced in the historical trajectory of resistance and the expression of indigenous sovereignty in the midst of major conflicts and migrations from their territory. We are interested in analyzing the challenges faced by the Atikum people in conquering their sacred territory, identifying the strategies of intergenerational resistance between 1993 and 2005. We seek to understand the interethnic links between indigenous people, whites and quilombolas in the Atikum people's struggle for sacred territory, considering the different contexts and spatialities; and how the different Atikum generations came out in defense of their sovereignty (intellectual, cartographic, religious) in the quest to preserve their knowledge/territory. The work is nourished by the voices of local thinkers, considering the analyses from the perspective of who we are, within an ancestralized sharing perspective, as well as indigenous authors, namely: Ailton Krenak, Gersem Baniwá, Daniel Munduruku, Graça Graúna, and Quilombola intellectual Nêgo Bispo. With a collective methodology centered on conversation circles, we realized that the tradition of telling is present in Atikum memory and is constituted in intergenerational relationships, which are led by both the master bees and the young bees. This dynamic between generations safeguards memories, history and identity and highlights the processes of resistance of the Atikum people who, in the midst of so much persecution, have managed to assert their sovereignty.